Answer:
![y =log_e(x+3)](https://tex.z-dn.net/?f=y%20%3Dlog_e%28x%2B3%29)
Step-by-step explanation:
It is given that the graph corresponds to a natural logarithmic function.
That means, the function
has a natural log (Log with base
) of some terms of x.
It is given that asymptote of given curve is at
. i.e. when we put value
, the function will have a value
.
We know that natural log of 0 is not defined.
So, we can say the following:
is not defined at
![\Rightarrow x+a =0\\\Rightarrow x = -a](https://tex.z-dn.net/?f=%5CRightarrow%20x%2Ba%20%3D0%5C%5C%5CRightarrow%20x%20%3D%20-a)
i.e.
is the point where ![y \rightarrow \infty](https://tex.z-dn.net/?f=y%20%5Crightarrow%20%5Cinfty)
a = 3
Hence, the function becomes:
![y =log_e(x+3)](https://tex.z-dn.net/?f=y%20%3Dlog_e%28x%2B3%29)
Also, given that the graph crosses x axis at x = -2
When we put x = -2 in the function:
![y =log_e(-2+3) = log_e(1) = 0](https://tex.z-dn.net/?f=y%20%3Dlog_e%28-2%2B3%29%20%20%3D%20log_e%281%29%20%3D%200)
And y axis at 1.
Put x = 0, we should get y = 1
![y =log_e(0+3) = log_e(3) \approx 1](https://tex.z-dn.net/?f=y%20%3Dlog_e%280%2B3%29%20%20%3D%20log_e%283%29%20%5Capprox%201)
So, the function is: ![y =log_e(x+3)](https://tex.z-dn.net/?f=y%20%3Dlog_e%28x%2B3%29)